Caracterização do sêmen de ariacó, Lutjanus synagris (LINNAEUS, 1758) - Vettorazzi, Mayra Bezerra (2012)
Aquaculture has become an important source of protein. Lutjanus synagris, lane snapper, is amongst the ten main species caught in the Brazilian central coast fisheries and, in the U.S., generated $ 157,745 in 2010. One of the prerequisites for the industry settlement of sustainable fish farming is the ability to control reproduction in captivity. The intensive breeding and artificial propagation requires appropriated technologies for gametes handling, which include short-term storage to supply the activity or even to improve its effectiveness. The knowledge of the species biology is important to complete the fertilization process and to develop techniques for semen storage in a short and long term. This study aim was to characterize quantitative and qualitatively the L. synagris fresh semen using the Computed Assisted Semen Analysis (CASA). Semen samples were analyzed regarding the sperm concentration, ejaculated volume, osmolality, pH, morphology, morphometry and sperm motility. The average sperm concentration, ejaculated volume, osmolality and pH was 2.43 ± 0.42 x 1010 sperm / mL, 0.39 ± 0.2 mL, 378.5 ± 65.1 mOsm / kg and 7.9 ± 0.17, respectively. L. synagris semen presented 34.6% of primary abnormalities and 24.25% of secondary abnormalities, the mean spermatozoa length, width, area and perimeter were3.06 μm, 2.73 μm, 7.63 μm2 and 9.70 μm, respectively. The total sperm motility of fresh semen was 78.8% being 22.32% considered of high velocity; the mean straightness and wobble were 63.24 and 67% respectively; the average of curvilinear velocity was 35.13 μm/s, the main straight line velocity was 13.04 μm / s, the main path velocity was 22.14 μm / s, the main lateral displacement of spermatozoa head was 2.84 μm and beat cross frequency was 4.04 Hz. The use of CASA for evaluation of sperm morphology and motility was successful and proved to be a practical method for the evaluation of large numbers of sperm.